Pathomorphological and biochemical study of the golden grey mullet Chelon auratus (Risso, 1810) in the waters of the southwestern Crimea (the Black Sea) - Gavruseva, T. V.; Sigacheva, T. B.; Chesnokova, I. I. (Marine Biological Journal, 2022)
The golden grey mullet Chelon auratus (Risso, 1810) (Mugilidae) is a valuable commercial and recreational species ranking first in terms of catch volume of the Black Sea indigenous mullets. The importance of this species in the regional fishery among demersal fish requires the development of a system for assessing its health status. Such research is based on an integrated approach involving biochemical and pathomorphological methods: these allow to investigate the alterations in fish prior the occurrence of visible manifestations, disruption of the processes of growth and reproduction, reduction of commercial size, and decrease in abundance. The aim of our work was to study both pathomorphological alterations and several biochemical parameters of golden grey mullet tissues for assessing its health status. Fish visual examination and pathological autopsy were carried out. For histological analysis, samples of the gills, liver, kidneys, gastrointestinal tract, spleen, and pancreas were fixed in Davidson’s solution and processed by standard methods. Based on the histological studies, the fish health status was investigated by a modified semi-quantitative analysis of alterations according to the Bernet et al. protocol and by assessing the distribution of lesion in organs using a scoring system. We determined the importance factors of alterations for C. auratus, the values of organ alteration indices, and the total index of fish pathology. The biochemical studies permitted to reveal the level of protein oxidation, lipid and urea peroxidation, and the activity of aminotransferases and alkaline phosphatase in the liver; moreover, we quantified albumin and glucose concentration in the blood serum. In the organs of the golden grey mullet, the histopathological alterations referring to four types of the reaction patterns were detected (circulatory disorders, regressive and progressive alterations, and inflammatory processes). Furthermore, parasites representing several species of different systematic groups (Protozoa, Monogenea, Trematoda, and Nematoda) were identified. It was established that the most severe histopathological alterations were caused by a parasitic protozoan, presumably Ichthyophonus sp. When carrying out a semi-quantitative analysis of alterations, the mullets were conventionally divided into conditionally healthy individuals and infected ones. Pathomorphological data were obtained, and the set of biochemical parameters was compared in these two groups. Significant differences were revealed in the values of organ alteration indices in C. auratus in the kidneys, liver, gastrointestinal tract, and pancreas. The values of the total index of fish pathology also differed significantly. The biochemical studies revealed a significant increase in urea content in the liver of fish from the group 2, that may indicate the kidney and gill excretory dysfunction (it was confirmed histologically). No significant differences were found in the level of lipid peroxidation, protein oxidation, and activity of aminotransferases in the liver of conditionally healthy and infected fish. The results of our investigation confirm high informativeness of the studied parameters for assessing the health status of the golden grey mullet.